Seed advantage in sport competitions: the case of professional judo (Revista de Artes Marciales Asiáticas, 2022)
The aim of this paper was to quantify the advantage granted to seeds in the case of professional judo knockout competitions. We used Monte-Carlo simulations to compute statistics including the probability of winning the competition, reaching the final or winning a medal in a standard draw compared to a random draw. We showed that the advantage given to seeds is often significant. As a result, misclassification in the ranking list is at a great disadvantage for top athletes that are not seeded. Interestingly, the advantage given to seeds appears robust as a function of parameters, such as sex or number of athletes, and modelling assumptions. Simulation is a flexible tool for athletes to take decisions in managing their position in the ranking list and to optimize their probability of success in major events.